Blending and Characterization of Polyolefin Nanocomposites for Coating Application - Santhoskumar*, A.U.; Saravanakumar, R.; Palanivelu, K. (Asian Journal of Chemistry, 2013)
In the present work nanocomposites comprising ultra high molecular weight high density polyethylene and low density polyethylene grafted by maleic anhydride using reactive extrusion method as the host polymers and organoclay filler were prepared by melt compounding. The dependence of their structure and morphology on the preparation condition was studied by X-ray diffraction and scanning electron microscopy. The blends were studied in three different ratios such as 90:10, 70:30, 50:50 of ultra high molecular weight high density polyethylene and low density polyethylene. The difference in mechanical and thermal properties was observed with the addition of the compatibilizer. Several percentages of compatibilizer were added and 5 % of its addition was found to be optimum. The nanocomposites of these blends were also studied with the addition of nanoclay. The resulting composites were evaluated in terms of mechanical properties, dispersion characteristics and thermal properties. Nanocomposite with 70:30 ratios with 3 % nanoclay showed optimum properties. This composite was uses for coating.